Banking Competition and Efficiency: Empirical Evidence from Sub-Saharan Africa. - Akambase, A.B. (University of Ghana, 2018)
This study aimed at evaluating the effects of competition on cost efficiency in the Sub-Saharan African (SSA) banking sector. The study also evaluated how competition affects bank cost efficiency in the various income classifications of countries in SSA. Due to the endogeneity issue between competition and cost efficiency, a two-stage least square method was employed to examine the data of 235 banks from 17 SSA during the period 2006-2012. The results of the study show evidence that competition and cost efficiency levels in SSA banking system are low and have been unstable over the study period, although they have improved marginally. There is also evidence of significant variations in cost efficiency of banks operating in the three different income groups of countries in SSA. Higher market power of banks in SSA banking industry is found to improve cost efficiency and, thus, it does not allow bank managers in SSA to enjoy a quiet life with no motivation to increase cost efficiency. Concerning the control variables, the coefficients of bank size and asset growth are positive and have no significant effect on bank cost efficiency. Market share, bank capitalization, Credit risk and asset growth square have a negative and significant effect on cost efficiency. The coefficients of inflation rate and Per capita GDP growth are positive and statistically significant. Regarding how competition affects cost efficiency of banks in the three-income classification of SSA countries, the findings reveal that competition is harmful to cost efficiency in low- and lower-middle income countries. However, it has no effect on cost efficiency in upper-middle income countries. The control variables in the various income groups of countries also exhibit different effects on cost efficiency in terms of significance and signs of coefficient and this suggests varied policy prescriptions.
MPhil.
Keywords: Banking; Sub-Saharan Africa